Creativity in education : a review - Spendlove, David (Design and Technology Education: An International Journal, 2008)
As part of a series of literature reviews that will occur within this and subsequent editions of the journal, this paper aims to locate a discussion of creativity in education within a discourse that is appropriate and accessible for design and technology (D&T) educators. In doing so, literature relating to: defining creativity; the context of creativity research and the relationship of design and technology and creativity, will be discussed. Inevitability, this review of creativity merely scratches the surface of a large body of literature and consequently some aspects of the topic have not been covered.